2023
DOI: 10.7759/cureus.36898
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Free Day of Surgery Discharge vs Overnight Observation Following Artificial Urinary Sphincter Placement

Abstract: IntroductionTo confirm the safety and examine outcomes of a day of surgery discharge following artificial urinary sphincter implantation in a population discharged without a catheter. MethodsWe retrospectively identified 110 patients, 31 of whom were discharged on the day of surgery, from a single surgeon following artificial urinary sphincter implantation. After institutional board review approval, patient charts were reviewed capturing demographics as well as three, thirty, and ninety-day outcomes. Further o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Similarly, this shift in practice is also evident among patients undergoing insertion of an artificial urinary sphincter (AUS) and has been demonstrated by early adopters of this practice. [1][2][3][4] Kozar et al reported a multi-institutional study evaluating postoperative catheter management after insertion of a first-time AUS. 5 The rates of urinary retention and complications were compared for patients leaving the procedure without a catheter vs those with a catheter in place for approximately 24 hours after AUS.…”
Section: Albany Medical Centermentioning
confidence: 99%
“…Similarly, this shift in practice is also evident among patients undergoing insertion of an artificial urinary sphincter (AUS) and has been demonstrated by early adopters of this practice. [1][2][3][4] Kozar et al reported a multi-institutional study evaluating postoperative catheter management after insertion of a first-time AUS. 5 The rates of urinary retention and complications were compared for patients leaving the procedure without a catheter vs those with a catheter in place for approximately 24 hours after AUS.…”
Section: Albany Medical Centermentioning
confidence: 99%